Efeitos cardiovasculares da associação entre baixas doses de cloreto de mercúrio e infarto do miocárdio em ratos - Faria, Thaís de Oliveira (2014)
Heavy metal exposure has been associated with several cardiovascular diseases, such as myocardial infarction (MI), and altered cardiovascular function is related to both the causes and consequences of MI. The aim of this study was to investigate whether chronic exposure to low doses of mercury chloride (HgCl2) enhances the functional deterioration of right ventricle strips and of aortic rings after MI. Male Wistar rats were divided into four groups: Control (vehicle), HgCl2 (exposure for 4 weeks: 1st dose 4.6 µg/kg, subsequent doses 0.07 µg/kg/day, i.m. to cover daily loss), surgically induced MI and combined HgCl2-MI. To characterize our experimental MI model, morphological and hemodynamic measurements were performed one week after MI. Isometric tension of right ventricle strips were investigated and vascular reactivity was evaluated in isolated aortic rings. Chronic HgCl2 exposure did not cause more injury than MI itself among the morphological or hemodynamic parameters evaluated. Regarding cardiac function, at basal conditions, despite similar maximum isometric force at L-max, relaxation time was increased in the MI group but unaffected in the HgCl2-MI compared to the Control group. Impairment of the sarcoplasmic reticulum (SR) function and reduction in the sarcolemmal calcium influx were observed in MI group associated with SERCA2a reduction and increased PLB protein expression. The combination of chronic HgCl2 exposure and MI did not cause any alteration in the developed force at Lmax, lusitropic function or -dF/dt except for a tendency of a reduction SR function. These findings could be partially explained by the normalization in the sarcolemmal calcium influx and the increase in NCX protein expression observed only in this group. These results suggest that chronic exposure to low doses of HgCl2 prevents the impaired SR function and the reduced sarcolemmal calcium influx observed in MI likely by acting on NCX, PLB and SERCA2a protein expression. Regarding vascular reactivity, the combination of chronic HgCl2 exposure and MI caused endothelial dysfunction by activating the oxidative stress pathway, which was confirmed after incubation with SOD (150 U/ml), apocynin (0.3 mM), allopurinol (100 µM) and catalase (1000 U/ml). Moreover, in the HgCl2- MI group, the vascular injury might also be correlated with reduced NO bioavailability, observed after L-Name administration (100 µM). Together, these findings explain the increased phenylephrine reactivity in animals from the HgCl2- MI group. Our results suggest that increased vascular xanthine oxidase ROS production represents an important mechanism of endothelial dysfunction in animals that have undergone chronic HgCl2 exposure plus MI injury and that this dysfunction is most likely caused by reducing NO bioavailability. In conclusion, these results emphasize that low level chronic mercury exposure might aggravate the injury induced by MI.